The Effectiveness of the Gasing Method Based on Multiplication Dice Games on Improving Elementary School Students’ Mathematics Learning Outcomes - Darlin Adam; Heri Yusuf Muslihin; Ika Fitri Apriani (Journal of Educational Sciences, 2026)
Low mathematics achievement at the primary school level in Indonesia remains a fundamental educational problem, as reflected in the 2023 National Assessment data, which shows that more than 60% of students have not yet reached the minimum numeracy competency standard. This condition highlights the urgent need for innovative, adaptive, and engaging learning approaches that can improve students' conceptual understanding of mathematics. This study aims to examine the effectiveness of the GASING (Easy, Fun, and Interesting) method combined with multiplication dice games in improving primary school students' mathematics learning outcomes. This research employed a qualitative approach using a Systematic Literature Review (SLR) method guided by the PRISMA framework. Data were collected from 31 relevant scientific articles published between 2015 and 2025 and analysed using thematic coding and descriptive analysis to identify key research patterns. The findings indicate that the GASING method improves students' understanding of basic mathematical concepts while creating a more interactive and enjoyable learning environment. In addition, multiplication dice games increase students' motivation, engagement, and active participation in mathematics learning. In conclusion, the integration of the GASING method and multiplication dice games represents an effective strategy for improving mathematics learning outcomes and fostering meaningful learning experiences for prima.